PANDUAN PROGRAM PENGEMBANGAN WISATA ALAM REGENERATIF DI DESA REROROJA, KECAMATAN MAGEPANDA, KABUPATEN SIKKA, PROVINSI NUSA TENGGARA TIMUR - Sawu, Michael Rudolfus (Jurnal Pariwisata Indonesia, 2025)
The development of regenerative nature-based tourism is a strategic approach that actively involves local communities as the main actors. This community service activity aims to formulate the direction of future tourism development programmes. This study employs a participatory action research approach, which includes the stages of problem identification, action planning, implementation, and reflection and evaluation. The results of the activity indicate that the tourism potential in this village can be developed through zoning mapping, the formulation of regenerative tourism programmes (including ecotourism, agrotourism, and adventure tourism) and the strengthening of community capacity through outreach and mentoring. The implications of this study suggest that a regenerative nature-based tourism approach can serve as an effective strategy for developing sustainable rural tourism destinations. It provides a foundation for formulating more inclusive and ecological village tourism development policies. Moreover, it serves as a practical reference for other regions aiming to develop tourism based on local wisdom and environmental conservation.